(untitled) (Economic studies journal, 2025)
of Libyan commercial banks. The research focused on five dimensions of credit risk disclosure: liquidity, capital adequacy, loan loss provisions, financial adequacy, and leverage. Financial performance was measured using two key indicators: Return on Assets (ROA) and Return on Equity (ROE). The study employed content analysis as the primary data collection method, extracting data from the annual reports of a sample of five Libyan commercial banks over the period from 2007 to 2021. An inductive approach was followed, utilizing a panel data model with three analytical techniques: Pooled Ordinary Least Squares (Pooled OLS), Fixed Effects Model, and Random Effects Model, all conducted through EViews 12 software. The results revealed a statistically significant positive effect of loan loss provisions on both ROA and ROE at a significance level of (α = 0.000). Conversely, capital adequacy and leverage exhibited a statistically significant negative impact on financial performance indicators at the same significance level (α = 0.000). Additionally, liquidity and capital adequacy showed no significant effect on financial performance at a significance level of (α = 0.05). Based on these findings, the study recommends enhancing the accounting disclosure of non-performing loans and their associated provisions by adopting more transparent and comprehensive disclosure policies, which would contribute to strengthening stakeholder confidence and achieving more stable and sustainable financial performance.